Behind the wheel: A bus driver’s literature review and future research directions - NAINIA Hoda,; CORNET Annie, (African Scientific Journal, 2025)
Abstract Despite being the backbone of public mobility, bus drivers often escape academic attention in management research. This study addresses the persistent neglect of bus drivers’ working conditions, focusing on their occupational environment, well-being, safety, and quality of life. Methodologically, a systematic comparative literature review was conducted using six international databases (Cairn.info, ScienceDirect, Web of Science, Academic Source Premier, Business Source Premier, and PubMed), applying inclusion criteria specific to bus and metro drivers and excluding unrelated professional categories. The final sample comprised 37 studies (36 peer-reviewed articles and 1 report) that investigated drivers’ working conditions, health outcomes, and occupational safety. Findings reveal that bus drivers endure irregular schedules, limited autonomy, and frequent passenger hostility. These stressors correlate with high turnover intentions, driven by work-related stress, low social support, and diminished professional fulfillment. Burnout symptoms emotional exhaustion, depersonalization, and reduced accomplishment are prevalent, alongside physical ailments such as musculoskeletal disorders and fatigue due to prolonged sedentary work and poor ergonomics. The main conclusion is that these working conditions heighten accident risks and compromise service quality, underscoring the urgent need for targeted interventions to improve workplace safety, enhance work-life balance, and reinforce social and professional support systems. Future research will delve deeper into this underexplored occupational group by adopting an ethnographic lens to closely observe the lived work trajectories of bus drivers, thereby generating grounded insights to inform sustainable policy and participatory management innovations. Keywords: bus driver, working conditions, occupational health and safety, job quality, ethnographic observation